2005
DOI: 10.1111/j.1467-9469.2005.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-validation Bandwidth Matrices for Multivariate Kernel Density Estimation

Abstract: The performance of multivariate kernel density estimates depends crucially on the choice of bandwidth matrix, but progress towards developing good bandwidth matrix selectors has been relatively slow. In particular, previous studies of cross-validation (CV) methods have been restricted to biased and unbiased CV selection of diagonal bandwidth matrices. However, for certain types of target density the use of full (i.e. unconstrained) bandwidth matrices offers the potential for significantly improved density esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
213
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(214 citation statements)
references
References 21 publications
1
213
0
Order By: Relevance
“…Second, since we incorporate downtown Denver as well as the surrounding areas such as Boulder and Greeley, and the Denver tech center, the study area is not single peaked. 16 Therefore, we estimate H using the smoothed cross validation (SCV) technique introduced by Hall et al (1992), which has been shown by Duong and Hazelton (2003) and Duong and Hazelton (2005b) to have a low Mean Integrated Square Error (MISE) for a range of target density shapes, an excellent convergence rate for small sample sizes, and an ability to accurately estimate the off-diagonal elements of the bandwidth matrix. The SCV bandwidth selection procedure is more formally discussed in Appendix 6.…”
Section: Measuring Place Specific Establishment Concentrationmentioning
confidence: 99%
“…Second, since we incorporate downtown Denver as well as the surrounding areas such as Boulder and Greeley, and the Denver tech center, the study area is not single peaked. 16 Therefore, we estimate H using the smoothed cross validation (SCV) technique introduced by Hall et al (1992), which has been shown by Duong and Hazelton (2003) and Duong and Hazelton (2005b) to have a low Mean Integrated Square Error (MISE) for a range of target density shapes, an excellent convergence rate for small sample sizes, and an ability to accurately estimate the off-diagonal elements of the bandwidth matrix. The SCV bandwidth selection procedure is more formally discussed in Appendix 6.…”
Section: Measuring Place Specific Establishment Concentrationmentioning
confidence: 99%
“…It is straightforward to see that UCV for the common kernel density estimator, with a uniform kernel as of Duong and Hazelton (2005) is given by…”
Section: Special Case When Transmetrics Are Metricsmentioning
confidence: 99%
“…In normal kernel density estimation, there are generally two methods that have received some attention, namely plug-in methods (Duong and Hazelton, 2003). and cross-validation methods (Duong and Hazelton, 2005). The plug-in methods require an analytic expression of the asymptotic mean square error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Härdle et al (2004)). In particular we employed the formulation of SCV method established by Duong and Hazelton (2005) and the algorithm proposed (an implemented) by Duong (2007). Besides the identification of features from a bivariate distribution it is of particular interest to quantify the directions in which these lay.…”
Section: Appendix a Data Preprationmentioning
confidence: 99%